Information-energy conversion process and the ecological bane of public administration in Nigeria - Abbo, Usman; Madu, Abdulrazak Yuguda (2020)
The generic interaction between Administrative institution and ecological variables is a topic which has generated a considerable amount of empirical inquiries and theoretical speculations within the field of Comparative Public Administration, where number of models and frameworks were advanced by scholars in attempt to established a sound theoretical footing to that aspect of Public Administration. One of such models is the Dorsey’s Information-Energy-Conversion which describes an Administrative system as developed to the extent that it possesses information and energy as well the capacity for its processing and the means for its conversion. The information-energy model focuses on the interaction of three ecological variables which are energy, information, and energy conversion and their relationship with Administrative system. This paper attempt to test the conceptual relevance of the Information-Energy Model in explaining the ecological predicaments of the Nigerian Public Administration. The paper developed and discussed a contextually driven schema where Information is configured to involve the societal attributes such as norms and values, sectionalism, ethnicity and sectarian sentiments prevailing within the Nigerian environment, Energy is constructed to indicate the labor force in the Nigerian Public Administrative institutions while Energy conversion is defined as the manpower training and development programmes within the Nigerian Public Administrative system. The paper argued that the predicaments of Public Administration in Nigeria is premised on the fact that the forces emanating from the ecological variables such as norms, values, sectarianism, ethnicity and schism (i.e. the information) plays greater role on its labor force (i.e. the energy) than the Administrative energy conversion process (manpower training and development), therefore administrative behaviour in Nigeria is a product of the Public official’s environment not the school or training he/she received.